Moringa Oleifera Seed As Coagulant And Coagulant Aid In Water Treatment - Oh, Yong Ping (Universiti Sains Malaysia, 2006)
The study investigated the use of Moringa oleifera seed as coagulant and coagulant aid in water treatment. Moring oleifera seed showed effectiveness as coagulant aid with alum in the clarification of turbid water. An amount of 60 % of alum can be saved when Moringa oleifera seed is used as coagulant aid for the Kerian river water (turbidity 15 – 90 NTU). Optimum dosage for combination of alum and Moringa oleifera seed extract was 10 mg/l and 8 mg/l, respectively. Highest turbidity removal was obtained at the pH of 7. Combination of aluminium sulphate and Moringa oleifera seed gave a much better and more consistent clarification.